الحدود الرقابية لعمل المحاكم المالية وسبل الإصلاح - الطاهري, سارة (جامعة الوادي University of Eloued, 2021)
إن الغرض من هذه الدراسة هو عرض الإكراهات التي تعيق الآداء الرقابي للمحاكم المالية بالمغرب(المجلس الأعلى للحسابات، المجالس الجهوية للحسابات) على مستويات عدة، سواء تلك المتعلقة بالإكراهات الداخلية(المؤسساتية، ضعف الموارد البشرية...) أو الخارجية (إكراهات ذات بعد سياسي، إداري، ثقافي). حيث وقفنا على مكامن الخلل واستعراض الحلول التي من شأنها تحسين الأداء الرقابي لهذه المحاكم، عن طريق من جملة من الإصلاحات ، لضمان فاعلية هذه الهيئة العليا للرقابة على المال العام بالمغرب. the purpose of this study is to present the constraints that hamper the audit performance of financial jurisdictions in Morocco (the Court of account , the regional Courts of accounts) at several levels, whether they are internal (institutional, weak human resources ...) or external (political, administrative, cultural constraints.) Where we examined the points of shortcomings and considered solutions that would improve the audit performance of these jurisdictions, through a series of reforms, to ensure the effectiveness of this Supreme Audit Institution of public fund control in Morocco.
limits of control over the work of financial jurisdictions and means of reform
مقال
Keywords: المحاكم المالية ; المجلس الأعلى للحسابات ; المجالس الجه ; ية للحسابات ; الرقابة ; المال العام